Establishment and characterization of a primary cell culture derived from external auditory canal squamous cell carcinoma. Issue 8 (29th June 2021) - Sekino, Yuki; Imaizumi, Akira; Komune, Noritaka; Ono, Mayumi; Sato, Kuniaki; Masuda, Shogo; Fujimura, Akiko; Koike, Kensuke; Hongo, Takahiro; Uchi, Ryutaro; Onishi, Hideya; Nakagawa, Takashi
Abstract : There are no human cancer cell lines of external auditory canal origin available for research use. This report describes the establishment of a culture condition for external auditory canal squamous cell carcinoma, derived from human tumor tissue. Successive squamous cell carcinoma colonies were dissociated by trypsin, subcultured, and maintained on a feeder layer (MMC‐TIG‐1‐20), yielding a clonally proliferating cell culture. Two morphological types of colony were observed: (a) densely packed colonies and (b) colonies with indistinct boundaries characterized by cell–cell complexes with fibroblast feeder cells. The SCC‐like characteristics of these cells were evidenced by positivity for p53, SCCA1/2, cytokeratin, and vimentin, and cancer stem cell properties were indicated by positivity for CD44, CD133, Oct3/4, and alkaline phosphatase (ALP). One of the unique properties of cell cultures is their tendency to form steric colonies in vitro on feeder layer cells. In addition, in the presence of fresh macrophages, the cells very slowly transform to break away from colonies as free cells, a process that resembles the epidermal–mesenchymal transition, whereby cell–cell interactions are weakened and migration activity is enhanced. These factors are purported to play a key role in cancer cell metastasis. Abstract : No human cancer cell lines of external auditory canal (EAC) origin are available for research use. This report describes the establishment of a culture condition for EAC squamous cell carcinoma (SCC). These cell cultures had cancer stem cell properties and tended to form steric colonies on feeder cells. These cell cultures could be used in future research on EAC‐SCC.